2014
DOI: 10.1103/physreva.89.053811
|View full text |Cite
|
Sign up to set email alerts
|

Bulk vortices and half-vortex surface modes in parity-time-symmetric media

Abstract: We demonstrate that in-bulk vortex localized modes, and their surface half-vortex ("horseshoe") counterparts self-trap in two-dimensional (2D) nonlinear optical systems with PT -symmetric photonic lattices (PLs). The respective stability regions are identified in the underlying parameter space. The in-bulk states are related to truncated nonlinear Bloch waves in gaps of the PL-induced spectrum. The basic vortex and horseshoe modes are built, severally, of four and three beams with appropriate phase shifts betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…There are fewer publications which reported PT -symmetric solitons in 2D settings [23,30,35]. The objective of the present work is to introduce a 2D network of horizontally coupled nonlinear dimers, which is a generalization of the 1D system from [39], and can also be realized in optics, using a photonic-crystal matrix into which nonlinear dual-core waveguides with the balanced gain and loss are embedded (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer publications which reported PT -symmetric solitons in 2D settings [23,30,35]. The objective of the present work is to introduce a 2D network of horizontally coupled nonlinear dimers, which is a generalization of the 1D system from [39], and can also be realized in optics, using a photonic-crystal matrix into which nonlinear dual-core waveguides with the balanced gain and loss are embedded (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, gap solitons in PT-symmetric media have drawn much attention. Li et al [13,14] even found stable PT surface gap solitons at the interface between a linear medium and a Kerr nonlinear medium. Cao et al [15] also reported stable PT gap solitons in a saturable self-defocusing nonlinear medium.…”
Section: Introductionmentioning
confidence: 97%
“…It was also mentioned in [10] that PT symmetry is a necessary condition for the existence of continuous modes in one-dimensional complex potentials. Ever since, PT-symmetric optical solitons [11][12][13][14][15][16] have been widely studied, including bright spatial solitons [17], gray solitons [18], dark solitons and vortices [19,20], multipeak gap solitons [21], nonlocal gap solitons * gelijuan26@gmail.com [22][23][24][25], vector solitons [26], and defect solitons [27,28]. Soliton families in PT-symmetric nonlinear lattices [29], in PT-symmetric mixed linear-nonlinear optical lattices [30], in PT-symmetric systems with quadratic nonlinearity [31], and in PT-symmetric couplers (the dual-core waveguide with balanced gain and loss) [32] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%